Health-resort industry in Ukraine : the underlying causes of changes - Nestorenko, Tetyana; Tokarenko, Olena; Nestorenko, Oleksandr (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Ukraine has great potential for the development of the health-resort industry, as there are rich natural complexes on the coast of the Black and Azov Seas, as well as the mountainous massifs of the Carpathians and Crimea. However, in recent years, the health-resort industry of Ukraine has been influenced by factors that negatively affected its development. The purpose of this research is to investigate the consequences for health-resort complexes of Ukraine of the annexation of Crimea by the Russian Federation and of an anti-terrorist operation being conducted in the east of the country. The paper analyzes the current state of the health-resort industry of Ukraine. Also, the authors discuss their distribution across the territory of Ukraine. They consider how changes in the state financing of health-resort treatment have affected the condition of the health-resort industry. Special attention is paid to the state of the health-resort complex of Donetsk and Luhansk regions, as parts of these territories are outside the control of the Ukrainian authorities. Based on data from open sources of information, the structure of health-resort complexes has been studied for the years 2013–2016
Keywords: uzdrowiska; Ukraina; tereny okupowane